miR-210 promotes the anti-inflammatory phenotype and M2 polarization in murine macrophages - Neculachi, Carmen Alexandra; Nastase-Rusu, Evelyn-Gabriela; Cherry, Laudy; Marinescu-Colan, Catalina Iolanda; Tastsoglou, Spyros; Cosman, Bogdan Paul; Popa, Alina Madalina; Panciuc, Cristina; Zaccagnini, Germana; Catrina, Sergiu Bogdan; Simionescu, Maya; Martelli, Fabio; et al. (Frontiers in Immunology, 2025)
IntroductionMacrophages play fundamental roles in immune regulation and tissue homeostasis, serving as one of the primary cell types that orchestrate tissue repair after injury. MiR-210 is a hypoxia-inducible, small non-coding RNA involved in regulating metabolic adaptation and inflammatory responses during normal repair processes. However, its role in macrophage polarization is not fully understood. Here, we report the impact of miR-210 deletion on macrophage polarization towards a pro-reparatory phenotype.MethodsBone marrow-derived macrophages were obtained from miR-210 knockout (KO) and wild-type (WT) mice and polarized toward the pro-reparative M2 phenotype. The transcriptomic profile of these cells, as well as their phagocytic capacity, cell energy phenotype, and cytokine production were assessed to determine the impact of miR-210 on the macrophage polarization process into a M2-like phenotype.ResultsCompared with their WT counterparts, miR-210 KO M0 macrophages presented a reduced glycolytic activity and a diminished metabolic flexibility. However, miR-210 KO cells exhibited increased phagocytosis in both M0 and M2 states, potentially as an adaptive response to their metabolic limitations. Transcriptomic analysis revealed distinct clustering between the M0 and M2 states, along with several notable differences in the transcriptional patterns between the two genotypes. Analysis of differentially expressed genes indicated an increased pro-inflammatory state in resting miR-210 KO macrophages compared to WT control cells. These data were further confirmed by the higher levels of IL-6, TNF-α, and IL-1b secreted by miR-210 KO M0 macrophages compared to WT cells. Analysis of the biological processes activated during the polarization process towards the M2 phenotype revealed an incomplete polarization of miR-210 KO cells, which may be attributed, at least in part, to reduced activation of mitotic regulators, leading to slower cell cycle progression and diminished proliferation.DiscussionOur data offers new insights into the role of miR-210 in promoting a macrophage shift toward the anti-inflammatory, pro-reparative M2 phenotype. The fine-tuned involvement of miR-210 in immune responses may have potential implications for chronic inflammation, immune dysfunction, and tissue repair.